Advances in manufacturing and materials engineering - Rahman, Mustafizur (Trans Tech Publications Ltd., 2012)
This collection of peer-reviewed papers is the fruit of a forum where institutions and industries could share ideas, innovations and problem-solving techniques. The 180 papers are grouped into: Material Removal Process; Forming Processes; Casting and Joining; Materials; High-Energy Beam Processing; Precision Engineering and Nanotechnology; Surface Engineering; Computer-Aided Engineering; Environmental Issues and Management in Manufacturing; Manufacturing Systems and Engineering; Value Analysis and Value Engineering; Fatigue and Fracture Mechanics